SCO‐792, an enteropeptidase inhibitor, improves disease status of diabetes and obesity in mice. Issue 10 (2nd July 2019) - Yashiro, Hiroaki; Hamagami, Kenichi; Hiyoshi, Hideyuki; Sugama, Jun; Tsuchimori, Kazue; Yamaguchi, Fuminari; Moritoh, Yusuke; Sasaki, Minoru; Maekawa, Tsuyoshi; Yamada, Yukio; Watanabe, Masanori
Abstract: Aims: Enteropeptidase is a serine protease localized on the duodenal brush border that catalyzes the conversion of inactive trypsinogen into active trypsin, thereby regulating protein breakdown in the gut. We evaluated the effects of SCO‐792, a novel enteropeptidase inhibitor, in mice. Materials and methods: In vivo inhibition of enteropeptidase was evaluated via an oral protein challenge. Pharmacological effects were evaluated in normal mice, in diet‐induced obese (DIO) mice and in obese and diabetic ob/ob mice. Results: A single oral administration of SCO‐792 inhibited plasma branched‐chain amino acids (BCAAs) in an oral protein challenge test in mice, indicating in vivo inhibition of enteropeptidase. Repeated treatment with SCO‐792 induced reduction in food intake and decrease in body weight in DIO and ob/ob mice. Plasma FGF21 levels were increased in SCO‐792‐treated DIO mice, an observation that was probably independent of reduction in food intake. Hyperglycaemia was markedly improved in SCO‐792‐treated ob/ob mice. A hyperinsulinaemic‐euglycaemic clamp study revealed improved muscle insulin sensitivity in SCO‐792‐treated ob/ob mice. SCO‐792 also improved plasma and liver lipid profiles and decreased plasma alanine transaminase, suggesting a potential treatment for liver diseases. Dietary supplementation with essential amino acids attenuated the effect of SCO‐792 on reduction in food intake and decrease in body weight in normal mice, suggesting a pivotal role for enteropeptidase in these biological phenomena. Conclusions: SCO‐792 inhibited enteropeptidase in vivo, reduced food intake, decreased body weight, increased insulin sensitivity, improved glucose and lipid control, and ameliorated liver parameters in mouse models with obesity and/or diabetes. SCO‐792 may exhibit similar effects in patients.